Al-Būṭī vs. Al-Qaraḍāwī: A Comparative Study of Thought on Al-Khurūj 'Alā Al-Ḥukkām - Muhammad Safwan Harun; Luqman Abdullah; Abdul Karim Ali; Muhammad Ikhlas Rosele; Saiful Islam Nor Mohd Zulkarnain; Syed Mohd Jeffri Syed Jaafar (UINSI Samarinda, 2026)
Non-Indexed Publication